EFFECT OF INFILL PATTERN DESIGN ON TENSILE STRENGTH OF FUSED DEPOSITION MODELLED SPECIMENS (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2025)
Deep knowledge of the connections between additive manufacturing design elements and the mechanical qualities of additive manufactured products becomes essential as the adoption of technology expands. Research analyses how the arrangement of material inside the printed object affects the tensile strength in specimens made through fused deposition modelling. The evaluation of 18 different infill patterns occurred through standardised tests, while technicians maintained identical processing parameters that included print temperature and both layer height and print speed. The test specimens underwent tensile testing for mechanical analysis. The test results indicate that the concentric pattern delivers maximum elastic modulus values at 1078 MPa, as well as a maximum tensile strength of 26.4 MPa which exceeds other patterns by 12-62% for modulus and 24-98% for strength. The elongation-at-break measurement of 10.5% is the best result for this pattern because it offers 10-338% more flexibility than competing structures. The elastic modulus (665 MPa) and the tensile strength (13.3 MPa) of the lightning pattern are the minimum among all tested patterns. The study also evaluated mass efficiency through strength-to-mass ratio calculations, with the concentric pattern achieving the highest value of 29.7 MPa/g, demonstrating superior weight-normalised mechanical performance alongside its absolute strength advantages. The study provides essential data on the performance-mechanical relationship of infill patterns that allow improvements to additive manufacturing processes to enhance structural integrity. These important results provide guidance for designers working on products that need particular mechanical characteristics.